EXPLORING THE FEMALE BILDUNGSROMAN THROUGH CHARLOTTE BRONTË’S JANE EYRE - Samatova Khadicha Rahmatullayevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper examines Charlotte Brontë’s Jane Eyre as a seminal example of the female Bildungsroman, highlighting the protagonist’s psychological, moral, and social development within the constraints of 19th-century Victorian society. The study investigates how Brontë subverts traditional gender norms through Jane’s journey toward selfhood, autonomy, and moral integrity. By analyzing literary techniques, character development, and thematic elements, the article demonstrates how Jane Eyre constructs a model for female empowerment and personal growth in literature. This research draws upon feminist literary criticism, historical context, and narrative analysis to situate Brontë’s work within the broader framework of the Bildungsroman genre. The findings indicate that Jane’s resilience, ethical consistency, and negotiation of social norms make the novel an enduring reference point in discussions of female identity and autonomy.